ANALYSIS OF VOLATILE ORGANIC COMPOUND OF MALLAWA HONEY - Sukmawati Sukmawati; Alfian Noor; Firdaus Zenta (Marina Chimica Acta, 2016)
This study aimed to determine the volatile organic compound for Mallawa honey. The quality of honey is determined from the nectar source, geographic location, and the processing technology. Volatile organic compound is one of the indicators in honey to determine the quality marker and this compound is formation aroma of honey.This research was done in three stages, namely the stage of sample preparation, extraction phase, and phase identification. Stages of sample preparation was performed to determine sampling locations, the determination of the location of the extraction and identification. Extraction is done in analytical chemistry laboratory Science Faculty, Hasanuddin University. Honey samples were extracted with n-heksan. The identification process carried out in an integrated laboratory Department of Chemical Science Faculty of Hasanuddin University, GCMS performed while the data in Forensik laboratory, POLRI. The results were obtained 35 volatile organic compounds, which are grouped into six classes of compounds, namely: hydrocarbons, acid, aromatic, ketones, aldehides and the other compounds